2015
DOI: 10.1136/bcr-2014-205635
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatous-lymphocytic interstitial lung disease and recurrent sinopulmonary infections in a patient with Good’s syndrome

Abstract: Good's syndrome is a rare primary immunodeficiency associated with adult thymoma. Complications are mainly autoimmune manifestations and recurrent infections with encapsulated bacteria. Only one possible case of combined granulomatous-lymphocytic interstitial lung disease (GL-ILD) and Good's syndrome have been described earlier, but the patient died at the time of diagnosis. This is the first case of GL-ILD in Good's syndrome with a successful outcome. We present a case of a 43-year-old man with GL-ILD, who su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…On the other hand, patients with underlying chronic granulomatous disease or defects in RAG1 or RAG2 may require hematopoietic stem cell transplantation (1719). GLILD can also be observed in patients with thymic defects, such as partial DiGeorge anomaly and Good syndrome (20, 21). These conditions remain important to diagnose because of other associated complications.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, patients with underlying chronic granulomatous disease or defects in RAG1 or RAG2 may require hematopoietic stem cell transplantation (1719). GLILD can also be observed in patients with thymic defects, such as partial DiGeorge anomaly and Good syndrome (20, 21). These conditions remain important to diagnose because of other associated complications.…”
Section: Discussionmentioning
confidence: 99%
“…Although the significance of GL-ILD in GS is not known at present because there have been only a few reported cases, it has become an important prognostic entity in patients with CVID, in whom an early diagnosis is considered essential to improving mortality and survival. 7 Noninfectious complications in immunodeficiency disorders are of major concern at present because of increasing mortality and morbidity. GL-ILD has become an important prognostic entity because of the worse prognosis observed in this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Only two cases reported in the literature showed GL-ILD associated with GS. 6,7 GL-ILD usually presents at the time of diagnosis or within the first 5 years after diagnosis, as was observed in CVID, and carries a worse overall prognosis. 5 The lung is the most commonly affected organ in GL-ILD, along with the spleen and lymph nodes.…”
Section: Clinical Findingsmentioning
confidence: 98%
“…Immunoglobulin therapy is often given as a first-line treatment to patients with GLILD, but in many cases, the effect is insufficient, and consequently, steroids and various immunosuppressants are required for further treatment. Hasegawa et al reported a case of GLILD for which immunoglobulin therapy was immediately effective for a lung lesion, and the authors suggested that the response to treatment might differ according to the histopathologic pattern and granuloma size (18). In our case, architectural distortions, such as pulmonary fibrosis and bronchiectasis, were not present, but the granuloma and LIP in the lesion suggested reversibility.…”
Section: Discussionmentioning
confidence: 53%